PENGARUH KEBUDAYAAN ASING DALAM PEMBENTUKAN RAGAM HIAS PELAMINAN NAREH PARIAMAN - Nofi Rahmanita (Institut Seni Indonesia Yogyakarta, 2012)
The Handicraft of embroidery “palaminan” in Nareh Pariaman is an old culture productwhich is used for social purposes. As the time goes, now, the “palaminan” is not only used by the kingor noblesse. Right now, it has been used in mostly wedding parties of Minangkabau tradition. It isused as the seat of the bride groom and bride who are called king and queen for a day. Regarding thistheme, when we see the several various of palaminan, it looks like been influenced by the Chinese andHindi/Gujarat Custom. Such as phoenix 9(bird) and lion decorated at the “palaminan”, or for theGujarat custom, there are embroidery with mirrors that decorate the palaminan. The mirrorembroidered for the people of Nareh Pariaman has the meaning “suluah bendang” in the village.The art of embroidery palaminan Nareh Pariaman has many structures which are connectedto each other. They can not be separated in each use. The structures are decorated by the many kindsof Minangkabau decoration. Most of the decorating comes from application of the Minangkabau’sphilosophy known as “alam takambang Jadi Guru”. The philosophy has symbolic meaning thatcontains some lessons about managing humans life, especially for people of Nareh Pariaman. Keywords: beyond culture, motif, pelaminan